Understanding the Determinants of Adoption of Healthcare Information Technology - AlSideiri A.; Cob Z.C.; Drus S.B.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Online pharmacies are often cited as an exemplar of evolving personal innovation in the physical health field, particularly in the areas of value-added information, consumer convenience and pharmacist outreach. Although online pharmacies have been widely adopted in developed countries, this trend has yet to catch on in developing nations like Oman due to the presence of numerous barriers. Unfortunately, there is a dearth of data regarding the factors that influence the acceptance and actual use of online pharmacies in Oman. By fusing the UTUAT-2 Theory with the TAM theory, this study proposes a conceptual model for understanding the factors that contribute to the growth of the online pharmacy industry in Oman. Three hundred and seventy-eight smartphone owners were asked to fill out a questionnaire. SPSS and the SEM method were used for data analysis.There was a significant correlation between the respondents Perceived Expectation (PE), Effort Expectation (EE), Technology Trust (TR), and Technology Awareness (TA) and the rate at which Online Pharmacy was adopted in Oman.We also discovered a moderating effect of BI on the decision to use an online pharmacy (OPA). Health literacy, consumer awareness, and the understanding needed to make informed health decisions are all areas that need to be strengthened for the successful adoption of Online Pharmacy at the highest levels of management and policymaking. 2023, IFIP International Federation for Information Processing.